2017
DOI: 10.1111/jocs.13231
|View full text |Cite
|
Sign up to set email alerts
|

Opening/closing pattern of Trifecta and Freestyle valves versus native aortic valve: Are stentless valves more physiologic than a stented valve?

Abstract: The Freestyle stentless valve was not superior to the Trifecta valve in terms of kinematics and functions more like a stented bioprosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Firstly, our previous studies showed that, in term of fluid dynamic, both at rest and under stress, and the leaflets kinematics the two valves were equal [12,38,39]. Secondly, the distribution of the stentless valves was 59% and 39% (p = 0.340) for "inappropriate" and "appropriate" groups respectively.…”
Section: Mass Regression Phenomenonmentioning
confidence: 94%
“…Firstly, our previous studies showed that, in term of fluid dynamic, both at rest and under stress, and the leaflets kinematics the two valves were equal [12,38,39]. Secondly, the distribution of the stentless valves was 59% and 39% (p = 0.340) for "inappropriate" and "appropriate" groups respectively.…”
Section: Mass Regression Phenomenonmentioning
confidence: 94%
“…There is no uniform consensus in labelling of valve prostheses' size, in vivo and in vitro testing and reporting of the haemodynamic performance and thrombogenicity that makes the comparison of the various valve models difficult [70]. The opening and closing mechanism of both mechanical and stented biological valves is different [71] from the physiological process based on currents returning…”
Section: Valve Replacement and Valve Reconstruction In Patients With mentioning
confidence: 99%
“…There is no uniform consensus in labelling of valve prostheses' size, in vivo and in vitro testing and reporting of the haemodynamic performance and thrombogenicity that makes the comparison of the various valve models difficult [70]. The opening and closing mechanism of both mechanical and stented biological valves is different [71] from the physiological process based on currents returning along the wall of aortic sinuses, described by Leonardo da Vinci in 1513 [72]. A pulmonary autograft (Ross-procedure) contains native leaflets along with their sinuses and it offers superb haemodynamics, proven growth potential and no thrombogenicity.…”
Section: Valve Replacement and Valve Reconstruction In Patients With mentioning
confidence: 99%
“…In vitro comparison of everting vs. non-everting suture techniques for the implantation of a supra-annular biological heart valve and potentially create turbulent flow patterns (4). Whereas stentless prostheses provide optimal orifice areas due to the lack of surrounding material and are supposed to maintain physiologic aortic root dynamics (5). However, the implantation of this valve type requires an experienced surgeon.…”
Section: Original Articlementioning
confidence: 99%